(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to identify the standard levels for the time of the emergence of the threshold distinguishing anaerobic in terms of testing (VO2max) in the device (Fitmate pro), and researchers used the descriptive method on a sample of players Baghdad clubs hand reel for the sports season 2014’s (62) player chosen intentional, was a homogeneity to them in the body mass index and ages time and training variables were applied maximum test consumption of the oxygen system device (Fitmate pro) them, the fact that the results bar for this test has a time of the emergence of the threshold distinguishing anaerobic, was processing the results extracting statistical features of this index and convert raw scores to grades standard (Alzaiah) and then to the standard grades amended, and then tab Results Bmdiat Mahddt and which has achieved (5) standard levels were conclusions of the study can not rely on modern hardware technology results to measure physiological indicators in the evaluation of the sports event that the standard levels of the results did not adopt, and that way The researchers realized that I use standard levels reliable in calendar time distinguishing the emergence of anaerobic threshold in terms of a test application (VO2max) device (Fitmate pro) to the handball players.